(untitled) (Research, Society and Development, 2021)
The insertion of herbal medicines in the form of mouthwashes for preventive and curative use in dentistry is a viable and promising alternative, due to the ease of access and costs. Plantago major is a medicinal plant whose leaves are used for inflammation of the mouth and oropharynx, as an antibacterial agent and antifungal agent. The use as a mouthwash has been implemented, being an adjunct to mechanical oral hygiene procedures. The objective was to report the effect of the Plantago major 7% aqueous solution as a daily mouthwash, in the control of dental biofilm and gingivitis. The patient reported pain in teeth 11 and 21, and gingival bleeding during oral hygiene. Clinical examination revealed active carious lesions, swollen gingival tissue with hyperemic areas. To characterize the clinical picture, the Lobene dental staining index, Löe & Silness gingival index and Turesky plaque index were applied. Areas with light stain, mild and moderate gingival inflammation (bleeding under pressure) and high scores on the Turesky plaque index were detected. After adequacy of the oral environment and dental prophylaxis, the patient was asked to rinse 10 mL of the Plantago major 7% solution, 2 times/day, for 1 month. Weekly clinical controls were performed. After 1 month, there was an absence of stains, a significant reduction in gingival inflammation and plaque rates, with no bleeding. There were no side effects. It was concluded that the Plantago major solution had an effective therapeutic profile in the control of dental biofilm, helping to restore oral health.